Exploratory study on the profitability framework of budget airlines in Asia. - Chan, Edwin Guo En. (2008)
This paper aims to derive a profitability framework for Asian budget airlines through an analysis of US and European budget airlines’ profit structure, an industry analysis of Asian aviation industry and an empirical study on consumers’ expectations to identify the key success factors of budget airlines in Asia.